PENGARUH STRUKTUR KEPEMILIKAN DAN FAKTOR LAINNYA TERHADAP REAL EARNINGS MANAGEMENT - LETISIA MARSHAFERINE; DEWI AGUSTINA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to provide empirical evidence related to the effect of ownership structure consisting of ownership concentration, managerial ownership, institutional ownership, and foreign ownership along with several other factors on real earnings management. Several other factors are profitability, firm size, and leverage. This research uses data from manufacturing companies that are consistently listed on the Indonesia Stock Exchange during 2019-2023 with a research period of 2021-2023. Sampling in this research used purposive sampling method. Data analysis in this research used multiple linear regression using the Statistical Package for the Social Sciences (SPSS) program. The results of this research indicate that foreign ownership, profitability, and firm size have an effect on real earnings management. However, other independent variables such as ownership concentration, managerial ownership, institutional ownership, and leverage have no effect on real earnings management.